Studi Komparatif Konsep Perdamaian (Ash-Shulhu) dalam Kitab Bulughul Maram dan Implementasinya pada Akad Kontemporer - Nuranisya, Siti; Najib, Moh (Sharia Journal and Education Center Publishing, 2025)
This research aims to analyze the legal standing and mechanisms of settlement (ash-shulhu) in muamalah (Islamic transactions) based on the perspective of hadith ahkam (legal hadiths). Amidst the complexity of modern economic disputes, peace settlements often emerge as a more effective solution than court litigation. This study employs a qualitative method with a library research approach and thematic analysis (maudhu’i) of hadiths related to reconciliation, specifically the hadith